Early Posttransplant Tryptophan Metabolism Predicts Long-term Outcome of Human Kidney Transplantation. Issue 8 (August 2015) - Vavrincova-Yaghi, Diana; Seelen, Marc A.; Kema, Ido P.; Deelman, Leo E.; van der Heuvel, Marius C.; Breukelman, Henk; Van den Eynde, Benoit J.; Henning, Rob H.; van Goor, Harry; Sandovici, Maria
Abstract : Background: Chronic transplant dysfunction (CTD) is the leading cause of long-term loss of the renal allograft. So far, no single test is available to reliably predict the risk for CTD. Monitoring of tryptophan (trp) metabolism through indoleamine 2.3-dioxygenase (IDO) has been previously proposed to predict acute rejection of human kidney transplants. Here, we investigate the potential of IDO/trp degradation along the kynurenine (kyn) pathway to predict the long-term outcome of human kidney transplantation. Methods: During the 2-year follow-up blood, urine, and kidney biopsies were collected from 48 renal transplant patients. Concentrations of kyn and trp in serum and urine were measured at 2 weeks, 6 months, and 2 years after transplantation. Kynurenine to tryptophan ratio was calculated as an estimate of trp degradation. To evaluate the histological changes and IDO expression, respectively, periodic acid schiff staining and immunohistochemistry for IDO were performed on biopsies taken at 6 months and 2 years. Results: Two years after transplantation, kyn/trp was increased in urine and decreased in serum as compared to 2-week values. In 2-year biopsies, IDO expression was mainly found in infiltrating inflammatory cells and in the glomeruli. The urine level of trp 2 weeks after transplantation predicted the serum creatinine 6 months and the estimated creatinine clearance 2 years after transplantation. Additionally, serum level of kyn 6 months after transplantation predicted the serum creatinine 2 years after transplantation. Conclusions: Early serum and urine levels of trp and kyn may offer a novel route for early detection of patients at risk for developing CTD. Abstract : Monitoring of tryptophan metabolism through indoleamine 2, 3-dioxygenase along the kynurenine pathway may predict the long-term outcome of human kidney transplantation.